Some Observations on the Evolution of Knowledge and Disciplines - Swarupanandan, K.; Sankara Pillai, K.; Basha, Chand (Journal of Information and Knowledge, 1996)
Epistemological aspects of what information and knowledge are, how they are acquired, how inferences and deductions are made, etc., have been dealt with at length in metaphysics and information sciences. On the other hand, what happens to the body of knowledge in the course of evolution, has been attempted to a little extent. The natural course of information development is traced. At least six different phases are recognizable: exploratory, classificatory, review, bibliographic, specialization and discipline branching phases. Very often, depending upon the discipline concerned, an application phase mayor may not be found. Of these, the classificatory and review phases have added importance in bringing development to the disciplines. If these phases are not properly developed, progress of the whole discipline is likely to be affected adversely. In this sense, ontogenetic studies of knowledge development in individual disciplines might be useful to understand the bottlenecks involved and to further the, progress. The processes and phases mentioned are of general applicability to all disciplines. Nevertheless, detailed study of individual disciplines might prove the absence of one or more or the phases mentioned or presence of additional phases not mentioned here. Attention is called for deeper studies in different disciplines so as to understand general and specific dimensions of knowledge building.